Modified SWCNTs with Amphoteric Redox and Solubilizing Properties. Issue 24 (7th May 2014) - Rodríguez‐Pérez, Laura; García, Raúl; Herranz, María Ángeles; Martín, Nazario
Abstract Invited for the cover of this issue is the group of Nazario Martín at Universidad Complutense de Madrid and IMDEA Nanoscience. The image depicts how doubly functionalized single‐wall carbon nanotubes (SWCNTs) can be switched from being soluble in aqueous solutions (with a Br− counteranion) to being soluble in organic solvents (with a PF6− counteranion). Read the full text of the article at 10.1002/chem.201400183.